Application of the Cooperative Learning Method in Improving Learning Achievement in Islamic Religious Education at SD Negeri 106226 Padang Baru - Sinaga , Loina; Sinaga, Masnauliana; Sidabukke, Hotrida (Jurnal Pendidikan Profesi Guru, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning using cooperative learning. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this research is elementary school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that cooperative learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with a breakdown of 40.19% in the pre-cycle, 75.37% in the first cycle and 89.82% in the second cycle. Thus, the use of cooperative learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning